A simple and rapid screening method for sulfonamides in honey using a flow injection system coupled to a liquid waveguide capillary cell - Catelani, Tiago Augusto [UNESP]; Toth, Ildiko Vargane; Lima, Jose L. F. C.; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier B.V., 2014)
A rapid and simple screening method was developed for the determination of sulfonamides in honey samples by flow injection analysis (FIA) coupled to a liquid waveguide capillary cell. The proposed method is based on the reaction between sulfonamides and p-dimethylaminocinnamaldehyde (p-DAC) in the presence of sodium dodecylsulate (SDS) in dilute acid medium (hydrochloric acid), with the reaction product being measured spectrophotometrically at lambda(max)=565 nm. Experimental design methodology was used to optimize the analytical conditions. The proposed technique was applied to the determination of sulfonamides (sulfaquinoxaline, sulfadimethoxine, and sulfathiazole) in honey samples, in a concentration range from 6.00 x 10(-3) to 1.15 x 10(-1) mg L-1. The detection (LOD) and quantification (LOQ) limits were 1.66 x 10(-3) and 5.54 x 10(-3) mg L-1, respectively. Positive and false positive samples were also analyzed by a confirmatory HPLC method. The proposed system enables the screening of sulfonamides in honey samples with a low number of false positive results, with fast response therefore offers a new tool for consumer protection. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Flow injection analysis (FIA); Screening; Sulfonamides; Liquid waveguide capillary cell (LWCC); Green chemistry